Rethinking Blackboard: teaching models for interactive learning - Booth, A; Kim, J (School of Hospitality and Tourism, Auckland University of Technology, 2015)
This paper considers alternative methods of teaching modules within the Blackboard delivery format demonstrating an interactive learning tool in a web based learning environment. We explore ways to go beyond simply training students in the use of digital tools and instead investigated an experiential approach to interactive learning. We adopted a content management systems (CMS) approach to transform teachers into facilitators for meaningful student engagement and the development of critical, creative, and ethical behaviour (Morellato, 2014, p. 185). Our prototype links Blackboard delivery into Cloud based learning. Our goal was to create an interactive platform in which students can share group work, while preserving the student’s own personal creations for future projects as e-portfolios to be shared with others, including perspective employers. The findings suggest that we have created a strong, student-focussed conceptual tool. Our conclusions and recommendations point to further areas of research and development required before our prototype is ready to be applied across Hospitality and Tourism education.
Keywords: Interactive learning; e:portfolios; Digital competence; Learning Management Systems; Cloud based learning; Agile learning